Creation and development of the local information computer network of Institute of High Energy Physics and Nuclear Physics NSC KIPT - Dudnik, V.A.; Krivorukov, E.V.; Kudrjavtsev, V.I.; Sereda, T.M.; Us, S.A.; Shestakov, M.V. (Вопросы атомной науки и техники, 2005)
Results and the basic stages of creation and development of local information computer network at Institute of High Energy Physics and Nuclear Physics NSC KIPT for last five years are submitted. The purpose of work was increase of an overall performance of researchers due to rational use of resources and creation on base local information computer network of shared system. In article obtained experience and specificity of realization of such systems is reflected.